Social acceptance of NIMBY facilities: A comparative study between public acceptance and the social license to operate analytical frameworks. (January 2023) - Xu, Min; Liu, Yong; Cui, Caiyun; Xia, Bo; Ke, Yongjian; Skitmore, Martin
Abstract: Not-In-My-Backyard (NIMBY) facilities play a significant role globally in the sustainable and healthy development of countries, and their successful introduction and operation has become increasingly critically influenced by local communities. Two mainstream research approaches have been proposed to enhance this, in the form of a "public acceptance" (PA) framework and a "social license to operate" (SLO) framework. However, the outcomes of social acceptance within the two approaches in typical NIMBY facilities in China have not been examined empirically. In response, this study introduces the emerging SLO framework, and discusses its applicability to the NIMBY facilities by a comparative analysis with PA, based on a questionnaire survey of residents (with a final sample size of 94) adjacent to a typical waste-to-energy (WTE) incineration plant located in Zhejiang province, China. The results show that, firstly, social acceptance assessed under the two frameworks is similar. Second, the community acceptance of Jiufeng case measured by SLO is non-linear and multi-dimensional, and there is a lack of institutional trust. Third, the viability of SLO is constrained by its social vulnerability and may occur through collective protests. These findings theoretically enrich the existing literature concerning social acceptance assessment and management of the dynamic industry-community relationships involved in the provision of NIMBY facilities. The findings will also be of practical value for government agencies and industrial sectors in gaining the social license needed from local communities. Graphical Abstract: ga1 Highlights: The SLO framework is applicable to evaluate the social acceptance of the WTE incinerator. The outcome of community acceptance measured by SLO is non-linear but lack institutional trust. The viability of SLO is constrained by its vulnerability and may occur through collective protests. The findings offer theoretical contributions and management implications for building SLO.